Synthesis of ethylene dichloride-based polysulfide polymers: investigation of polymerization yield and effect of sulfur content on solubility and flexibility. (2nd January 2021) - Sheydaei, Milad; Talebi, Saeid; Salami-Kalajahi, Mehdi
Abstract : In this work, a series of polysulfide polymers were synthesized using organic monomer (ethylene dichloride) and sodium-based aqueous monomers via interfacial polymerization. The structural characteristics of aqueous monomers and synthesized polysulfide polymers were identified by Fourier transform infrared (FT-IR), Raman, and ultraviolet–visible-near infrared (UV–VIS-NIR) spectroscopies. The Optimum temperature of polymerization was obtained at 75°C. Benzyltriethylammonium chloride (BTEACl) and tetrabutylammonium bromide (TBAB) were used as phase transfer catalysts (PTC) where BTEACl showed better performance regarding the polymerization yield. Moreover, adding ethanol to polymerization media increased the polymerization yield significantly. The results showed that along with increasing sulfur in the structure of polymers, solubility and flexibility were increased whereas it decreased the hardness, melting point ( Tm ) and glass transition temperature ( Tg ) of obtained polymers. GRAPHICAL ABSTRACT: